Mechanisms of Cancer-Associated Thrombosis: Role of Cancer-Derived Exosomes - Abdol Razak, Norbaini Binti (Curtin University, 2024)
This thesis investigated the effect of pancreatic cancer-derived exosomes on cells that are known to play roles in thrombosis. Together, the results demonstrate that PDEx have a range of effects on neutrophils, platelets and endothelial cells. Overall they can modulate the function of these cells to have procoagulant properties, suggesting that PDEx has a significant function in promoting thrombosis and can potentially be targeted for therapeutic intervention cancer-associated thrombosis.